„Problems that occur during construction project realization in Republic of Macedonia“ - Zileska-Pancovska V., Ristevska-Jovanovska S., Mijoski G. (BRNO UNIVERSITY OF TECHNOLOGY, FACULTY OF CIVIL ENGINEERING, 2012)
Construction project realization is a complex process that is determined by numerous changeable factors that are in interaction. These factors are the source for many problems that occur during the construction project realization in Republic of Macedonia. In the paper the sources for problems are grouped and analyzed in three groups. The first group is consist of factors related to external construction project influences, such as: economy, politic, law, socio-cultural conditions etc. The second source of problems is related to the factors relevant to structure location and its surrounding, such as: topography, geotechnical factor, climate, ecology and other factors. The third group is connected with participants in construction project realization: Investor, Contractor, Designer, Supervisor, Consultant and other participants. Past and current situation about these three sources of problems are analyzed in the paper. The findings are supported by the survey data. The survey cover participants in construction project realization in Republic of Macedonia. The analyze findings are the base for suggestions that are gave about the construction project’ realization problems solving
Keywords: construction project, realization, problems